2016
DOI: 10.1007/s10549-016-3768-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in male breast cancer: a population-based study

Abstract: Prognostic factors in male breast cancer (MaBC) are controversial. The objective of this study was to analyze patient characteristics and prognostic factors in MaBC over the last decade. Using the Surveillance, Epidemiology, and End Results program, we extracted MaBC patients diagnosed between 2003 and 2012. Patient characteristics were compared between tumor grades. We conducted univariate and multivariate analyses to determine the effects of each prognostic variable on overall survival (OS). The study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
31
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 21 publications
19
31
3
Order By: Relevance
“…Moreover, in subgroup analysis, the expression of TAZ/CTGF and YAP/CTGF conferred poorer overall survival in patients with G3 tumors, but not in those with G1-2 tumors. In the entire population ( N = 129), higher tumor grade seemed to be also associated with shorter survival, and this is consistent with an independent study that analyzed survival outcomes of ~3.000 MBC patients [51]. A plausible hypothesis is that TAZ/YAP activity may be also necessary for maintenance/amplification of the CSC compartment in MBC.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, in subgroup analysis, the expression of TAZ/CTGF and YAP/CTGF conferred poorer overall survival in patients with G3 tumors, but not in those with G1-2 tumors. In the entire population ( N = 129), higher tumor grade seemed to be also associated with shorter survival, and this is consistent with an independent study that analyzed survival outcomes of ~3.000 MBC patients [51]. A plausible hypothesis is that TAZ/YAP activity may be also necessary for maintenance/amplification of the CSC compartment in MBC.…”
Section: Discussionsupporting
confidence: 83%
“…Leone et al found that age at diagnosis, tumor grade, stage, surgery, radiotherapy, ER, and marital status have a clear impact on OS in MBC 12. Masci et al suggested that grade III and Ki-67>20% were associated with shorter OS 23.…”
Section: Discussionmentioning
confidence: 99%
“…The median diagnosis age of MBC is 68 years and it is 5–10 years later than FBC 6. While the mortality rate of MBC improved in the last 30 years,11 the overall 5-year and 10-year survival rates are 70.6% and 53.7%, respectively 12. Thus, MBC is a disease that cannot be ignored and requires extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…Although tamoxifen is a beneficial treatment, it is not without clinical issues including side effects such as reduced libido and impotence (Arnould et al 2006), which may lead to a clinical or patient decision to stop treatment (Fentiman et al 2006). In addition, the prognostic indicators are not necessarily the same between male and female breast cancers, making it difficult to determine which patients truly require treatment (Abreu et al 2016, Leone et al 2016.…”
Section: Clinical Featuresmentioning
confidence: 99%